Pengaruh Budaya Organisasi dan Kompensasi terhadap Komitmen Organisasi: (Studi pada PT INKA Multi Solusi) - Arden Stalin Lubanov Fakhrullah; Ika Korika Swasti (Al-Buhuts, 2024)
The research was conducted to analyze the influence of organizational culture and compensation on organizational commitment at PT INKA Multi Solusi. The research method used was quantitative research. The sampling technique employed non-probability sampling method with a saturated sampling of 70 permanent employess in non-production units. Data collection was carried out through questionnaire distribution. The data from the respondents in the study were processed using partial least square. The research results indicate that organizational culture has a significant positive impact on organizational commitment. Compensation has a significant positive impact on organizational commitment. The results obtained show that the better the implementation of organizational culture in the company, the higher the organizational commitment of employees and the higher the compensation provided by the company, the higher the organizational commitment of PT INKA Multi Solusi employees.